Functional Outcome of Minimally Invasive Percutaneous Plate Osteosynthesis in Distal Tibial Fracture - Gurung, Bijaya; Karki, Prashanna Dip; Thapaliya, Ritesh; Waiva, Surya Bajra Lama; Shah, Krishna Jung; Kathayat, Tufan Singh; Dutta, Deepak; Paudel, Santosh (Journal of Karnali Academy of Health Sciences, 2024)
Background: Traditional plating technique for distal tibia fractures may produce periosteal stripping and microcirculatory damage, which may frequently induce infection, nonunion or both. Treatment of these injuries using minimal invasive percutaneous plate osteosynthesis (MIPPO) technique may minimize soft tissue injury and damage to the vascular integrity of the fracture fragments. The objective of our study was to assess the clinical result of MIPPO for distal fracture of tibia.Methods: A total of 30 patients of distal tibia fracture treated with MIPPO with Locking compression plate (LCP) Technique at National Trauma Center, Kathmandu were studied during a period of one year. Patients were followed up on 2nd post-operative week and then at an interval of 4 week till 6 months. Tenny and Weiss clinical assessment criteria was used in each follow up.Results: In our study, mean age of the patients was 36.9 year with standard deviation ± 9.4 and majority of them were male (60%). The mean time for radiological union of bone was 17 weeks. In final follow up, 2 cases had excellent result, 23 cases had good result and 5 cases had fair result. No case had poor functional outcome.Conclusion: MIPPO offers a reliable and reproducible technique for treating distal tibia fractures with intra-articular or peri-articular fracture extension. This technique avoids significant complications encountered with more commonly used internal and external fixation techniques for such injuries. This procedure is associated with good functional outcomes regarding the ankle range of motion.